Profile of student ability of science literacy in biology at the second grade of junior high school state in Mataram District Indonesia - Ayudya Lestari; Dadi Setiadi; I Putu Artayasa (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This research aims to describe the student ability of science literacy in Biology at the second grade of Junior High School State in Mataram district Lombok Island Indonesia. This research used a qualitative descriptive method. The subject of this research was second-grade students. The data collection technique used the instrument ability of science literacy test regarding indicators competence of science literacy. The technique of data analysis was done descriptively. These results show that the student ability of science literacy at 53.7. At the same time, students' achievement is dominated by the aspect of competence in evaluating and designing investigation scientifically at 65.5%. The average in the element of competence explains the phenomenon scientifically at 49.2%, and the lowest competence in interpreting data and evidencing scientifically at 45.8%. Therefore, the student ability of science literacy of Junior High School state in Mataram sub-district including the low category.